Early development of executive functions: A differential study - Sastre i Riba, Sylvia; Fonseca-Pedrero, Eduardo; Poch-Olivé, María Luisa (Anales de Psicología / Annals of Psychology, 2015)
The ontogeny of executive functions is essential to explain differential and normative developmental trends. Executive functions must be studied from early ages because of their consequences on mental flexibility, monitoring information, planning, and cognitive control. We propose a differential study in alternative developmental courses: typical babies, Down Syndrome babies, and babies with risk-factors at birth (congenital hypothyroidism and low weight). Applying Systematic Observational Methodology, spontaneous babies’ activity was registered. The results indicated that: a) Typical babies showed best shifting, action flexibility to obtain a goal, and results; b) Among risk-babies, the lower efficacy in executive functioning was observed on low birth weight babies, the hypothyroidism ones are closer to the typical babies; c) low birth weight babies showed a good level combining actions, but they obtain less results; d) Down Syndrome babies showed more executive functioning difficulty, lower flexibility, high perseveration and less error detection.